2006
DOI: 10.1111/j.1442-2042.2006.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of vesicouterine fistula by luteinizing hormone‐releasing hormone analog

Abstract: Vesicouterine fistula is a rare complication of cesarean section. Although surgical repair was mandatory for the management of the fistula previously, a recent review showed high efficacy of hormonal manipulation by the induction of amenorrhea. Herein, we report a new case of vesicouterine fistula secondary to cesarean section successfully treated by luteinizing hormone-releasing hormone analog for 6 months. Conservative hormonal treatment for vesicouterine fistula caused by cesarean section should be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…Graziotti et al [7] reported healing of small immature fistulas discovered soon after the cesarean section by prolonged indwelling catheterization or fistula tract fulguration. Hemal et al [8] and Yokoyama et al [9] reported the successful treatment of some of these fistulas by hormonal induction of menopause using either oral contraceptive pills or GnRH resulting in involution of the puerperal uterus. Lowering the menstrual flow across the fistula tract may be the possible reason for spontaneous healing of the fistula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graziotti et al [7] reported healing of small immature fistulas discovered soon after the cesarean section by prolonged indwelling catheterization or fistula tract fulguration. Hemal et al [8] and Yokoyama et al [9] reported the successful treatment of some of these fistulas by hormonal induction of menopause using either oral contraceptive pills or GnRH resulting in involution of the puerperal uterus. Lowering the menstrual flow across the fistula tract may be the possible reason for spontaneous healing of the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Management options for these fistulae vary from prolonged catheter drainage [7] to hormonal manipulation [8,9] and open surgical and laparoscopic repairs [10][11][12][13][14] . The transabdominal approach is the only way to repair VUF, as it cannot be accessed vaginally.…”
Section: Introductionmentioning
confidence: 99%
“…Other conservative measures include hormonal therapy (eg, medroxyprogesterone, combined oral contraceptives, leuprorelin acetate), which has been used to induce amenorrhea by hormonal manipulation and been found to be an effective, noninvasive, and conservative method of VUF management [20][21][22][23][24]. It is believed that lowering menstrual flow across the fistula allows for healing.…”
Section: Management Of a Vufmentioning
confidence: 99%
“…Medical treatment involving the use of hormones to induce amenorrhoea especially for small fistulas has been advocated in the literature [3,15]. Surgery however is the definitive treatment of vesicouterine fistula [3].…”
Section: Previous Cs No Previous Cs Totalmentioning
confidence: 99%
“…Conservative treatment entails the use of indwelling catheter immediately following delivery. Medical treatment involves the use of hormones to induce amenorrhoea especially for small fistulas [3,15]. Surgery is definitive and involves vaginal, transvesical, transperitoneal and laparoscopic approaches [3].…”
Section: Introductionmentioning
confidence: 99%